2020
DOI: 10.1002/nvsm.1695
|View full text |Cite
|
Sign up to set email alerts
|

Empathy from private or public self‐consciousness in socially responsible consumption

Abstract: The issue of socially responsible consumption (SRC) has been discussed from a perspective of behavioral change. Empathy is a moral emotion to motivate this behavioral change and includes cognitive and affective elements. Yet, the process of how an individual generates empathy cognitively and affectively is still unclear. Therefore, the main aim of this research is to discuss two types of self‐consciousness which result in empathic concern that changes consumers' behavior to be more socially responsible. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…Consider first the case when public self‐consciousness of the consumer is high. Past research has shown that people with high public self‐consciousness exhibit more empathetic behavior due to their motivation to maintain a positive self‐image in the eyes of others (Luan & Chen, 2021; Nook et al, 2016). We had argued earlier that low‐control consumers are likely to experience negative affect, which they seek to counteract with sources of positive affect such as anticipated warm glow from helping local sellers.…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…Consider first the case when public self‐consciousness of the consumer is high. Past research has shown that people with high public self‐consciousness exhibit more empathetic behavior due to their motivation to maintain a positive self‐image in the eyes of others (Luan & Chen, 2021; Nook et al, 2016). We had argued earlier that low‐control consumers are likely to experience negative affect, which they seek to counteract with sources of positive affect such as anticipated warm glow from helping local sellers.…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…As for the behavior aspect, sustainable behavior can be compared with conventional behavior, such as purchase decision of sustainable versus conventional products (Schultz et al, 2023). Sustainable behavior is socially responsible, since it contains altruistic and unselfish concern (Luan & Chen, 2021). Specifically, beach cleaning is based on altruistic values (Power, 2022).…”
Section: Sustainable Behavioral Intentions and Purchase Of Cause-rela...mentioning
confidence: 99%